Semiconducting Metal Oxides for Gas Sensing - Deng, Yonghui (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the use of semiconducting metal oxides as gas sensing materials, including the sensing mechanism and sensing materials modification approach, while also providing a comprehensive introduction to semiconductor gas sensing devices. As an essential part of IoT (Internet of things), gas sensors have shown great significance and promising prospects. Therefore, studies on semiconducting metal oxides, one of the most important gas sensing materials, have increasingly attracted attention from various disciplines. The book offers a valuable reference guide to metal oxide gas sensing materials for undergraduate and graduate students alike. It will also benefit all researchers who investigate metal oxides nanomaterials synthesis and gas sensing with relevant frontier theories and concepts. Engineers working on research and development for semiconductor gas sensors will also find new ideas in sensor design. .